The Carousel Concept as Assemblage Acting * - Tranholm, Mette (Peripeti, 2021)
Since 2004 performer and acting teacher Marion Reuter has developed the carousel concept referring to an improvisation method for training multiple acting techniques and scenic functions. This article is based on my collaboration with Reuter and unfolds how my disincarnation theory of assembling different acting techniques enhances Reuter’s carousel practice and vice versa. The collaboration provided an opportunity to try out my theory in practice. The article and the collaboration are part of an artistic research project about the carousel concept at The Danish National School of Performing Arts (DDSKS) led by Marion Reuter. I acted as documentarist and dramaturge. The empirical backdrop for the article consists of my observations and discussions of Reuter and her students’ work on the floor with the carousel concept during the spring of 2018 at DDSKS and a video recording of an earlier carousel ride with students from DDSKS. Our artistic research is characterized by the collaborative exchange between an artistic practice – the carousel concept – and the performance theoretical concept of character which I call disincarnation. The main goals were to document and develop a vocabulary for the carousel concept, thus improving the training, knowledge, and reflection practice of acting students.